Electrode couple for water softening and application method thereof

By designing electrode pairs, setting up water flow channels and precious metal catalyst layers in the water treatment system, efficient water softening and resin regeneration were achieved, solving the problems of limited resin contact area and dependence on high-concentration brine, and improving resin utilization and system stability.

CN121672791APending Publication Date: 2026-03-17GREE ELECTRIC APPLIANCE INC OF ZHUHAI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610083032.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-21
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

When existing ion exchange resins are used in the form of particle packing, the contact area between the resin and water is limited and the utilization rate is not high. The regeneration process is highly dependent on high concentrations of brine, resulting in low resin material utilization and increased operating costs.

Method used

An electrode pair is designed, including a positive electrode and a negative electrode, with a water flow channel. The positive electrode and the negative electrode are respectively an OH- type anion exchange resin layer and an H+ type cation exchange resin layer. A noble metal catalyst layer is set in the negative electrode. Resin regeneration is achieved by reversing the electrode voltage, reducing the dependence on external regeneration medium.

Benefits of technology

It improves the migration efficiency of ions in water and the utilization rate of electrode surfaces, enhances the targeting and efficiency of the water softening process, reduces the dependence on high-concentration brine regeneration, improves the regeneration efficiency of the resin layer and the recycling capacity of the electrode pairs, and enhances structural stability and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672791A_ABST
    Figure CN121672791A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment, in particular to an electrode pair for water softening and an application method thereof.The electrode pair comprises a positive electrode and a negative electrode, and a water passing channel is formed between the positive electrode and the negative electrode; the positive electrode comprises a current collector as well as a supporting middle layer and a resin layer which are sequentially attached to the current collector, and the negative electrode comprises a current collector as well as a catalyst layer, a supporting middle layer and a resin layer which are sequentially attached to the current collector; the resin layer of the positive electrode is an OH-type anion exchange resin layer, and the resin layer of the negative electrode is an H + type cation exchange resin layer; the support middle layer comprises a binder and conductive powder with the particle size of 100-800 meshes; the catalyst layer includes a noble metal catalyst. The catalyst layer is arranged in the negative electrode, the reverse electrode is the positive electrode during regeneration, water is subjected to in-situ electrolysis under the action of an electric field to generate regenerated ions, and resin recovery is achieved together with the electrolysis action of the negative electrode during regeneration; and meanwhile, the supporting middle layer is matched, so that the adhesion stability of the resin layer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water treatment technology, and more specifically to an electrode pair for water softening and its application method. Background Technology

[0002] Water commonly contains hardness ions such as calcium and magnesium ions. The presence of these hardness ions can adversely affect daily and industrial water use, for example, reducing washing efficiency, forming scale on the inner walls of pipes and heat exchange equipment, thus reducing thermal efficiency, and potentially causing skin irritation. Therefore, water softening treatment to reduce the content of hardness ions has become an important requirement in both domestic and industrial water use.

[0003] In existing technologies, water softening typically relies on ion exchange resins. The basic principle is to utilize the exchangeable ions in the resin to exchange with hardness ions in the water, thereby removing the hardness ions. Current water softeners generally use granular sodium-type cation exchange resins, operating in a resin bed configuration for softening. Once the resin reaches saturation, a high-concentration brine solution needs to be introduced to regenerate it and restore its ion exchange capacity.

[0004] However, the above-mentioned softening methods still have certain shortcomings in practical applications. First, granular resin is usually packed into the resin tank in a stacked manner, and the water flows in the gaps between the resin particles, resulting in high hydraulic resistance and limited effective contact area between the resin and the water, leading to low resin utilization. Second, the resin regeneration process requires continuous consumption of high-concentration brine, which increases the system's operating costs and complexity, and is not conducive to long-term stable operation.

[0005] Therefore, it is still necessary to provide a new water softening material and its preparation method that can improve the utilization rate of resin materials, reduce the dependence on high-concentration brine regeneration methods, take into account the structural stability under electrochemical regeneration conditions, and enhance the comprehensive removal capacity of multiple ions in water to meet the application needs of salt-free soft water and comprehensive water purification. Summary of the Invention

[0006] This invention provides an electrode pair for water softening and its application method, in order to solve the problems of limited contact area between resin and water, low resin utilization rate, and high dependence on high-concentration brine in the regeneration process when ion exchange resin is used in the form of particle stacking in the prior art.

[0007] In a first aspect, the present invention provides an electrode pair for water softening, comprising a positive electrode and a negative electrode, wherein a water flow channel is formed between the positive electrode and the negative electrode. The positive electrode includes a current collector and a supporting intermediate layer and a resin layer sequentially attached to the current collector; the negative electrode includes a current collector and a catalyst layer, a supporting intermediate layer and a resin layer sequentially attached to the current collector. The resin layer of the positive electrode is OH - The anion exchange resin layer of the negative electrode is H-type. + The cation exchange resin layer comprises a binder and conductive powder with a particle size of 100-800 mesh; the catalyst layer comprises a noble metal catalyst.

[0008] It should be noted that the terms "positive electrode" and "negative electrode" are functional designations, and their correspondence is defined based on the water softening process. Specifically, during the water softening process, when direct current is applied, the electrode on the side with negative current is defined as the negative electrode, and the electrode on the side with positive current is defined as the positive electrode. The negative electrode includes a current collector and a catalyst layer, a supporting intermediate layer, and a resin layer that are sequentially attached to the current collector.

[0009] During the resin regeneration stage, by applying a reverse voltage to the electrode pair, the electrode originally defined as the negative electrode in the softening stage is converted to a positively charged state and used as the positive electrode in the regeneration stage. Therefore, the negative electrode does not refer to an electrode that is structurally permanently in a negative state, but rather to an electrode that carries a negative charge during the water softening process, and its polarity can be switched between the softening and regeneration processes according to the operating conditions.

[0010] By setting up a water flow channel between the positive and negative electrodes, the water to be treated can flow directionally along the water flow channel under the action of an electric field, which is beneficial to improving the migration efficiency of ions in the water and the effective utilization rate of the electrode surface.

[0011] OH groups were respectively placed at the positive and negative electrodes. - Type anion exchange resin layer and H + The cation exchange resin layer allows anions and cations in the water to migrate directionally under the influence of an electric field and be selectively removed by the corresponding resin layer, thereby enhancing the specificity and overall efficiency of the water softening process.

[0012] A catalyst layer is placed in the negative electrode to promote the electrolysis reaction of water through a noble metal catalyst. During operation and regeneration, active ions for resin regeneration are generated in situ, reducing dependence on external regeneration media and improving the regeneration efficiency and recycling capacity of the electrode pair. At the same time, a supporting intermediate layer composed of binder and conductive powder is placed between the current collector and the resin layer. This ensures the conductivity of the electrode while enhancing the adhesion stability of the resin layer and mitigating the risk of delamination caused by water absorption and swelling of the resin material. This is beneficial to improving the structural stability and service life of the electrode pair under long-term operating conditions.

[0013] In one optional embodiment, the thickness of the catalyst layer is 0.05-50 μm; for example, thicknesses of 0.05 μm, 1 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, and 50 μm.

[0014] In one optional embodiment, the wet thickness of the support intermediate layer is 0.1~1 mm; for example, the wet thickness of the support intermediate layer is 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.8 mm, or 1 mm.

[0015] In one optional embodiment, the wet thickness of the resin layer is 0.2~0.8 mm; for example, the wet thickness of the resin layer is 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, or 0.8 mm.

[0016] In one optional embodiment, the catalyst layer comprises one or more of elements such as platinum, iridium, and ruthenium, and their metal oxides; Preferably, the catalyst layer is fixed on the current collector by deposition, spraying, or sintering.

[0017] In one alternative embodiment, the mass ratio of conductive powder to binder in the supporting intermediate layer is (50%~95%):(5%~50%).

[0018] In one optional embodiment, the conductive powder includes one or both of graphite powder and graphitized carbon fiber powder. In one alternative embodiment, the adhesive comprises one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyethersulfone (PESU), polysulfone (PSU), and polyimide (PI).

[0019] In one optional embodiment, the method for preparing the supporting intermediate layer includes the following steps: S1 mixes conductive powder and binder with organic solvent to form a support interlayer slurry; S2 The supporting intermediate layer slurry is coated on the surface of the current collector and cured to obtain the supporting intermediate layer.

[0020] In one optional embodiment, the organic solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, and ethanol; In one optional embodiment, based on the total raw material mass of conductive powder and binder, 0.5 to 6 mL of organic solvent is added for every 1 g of total raw material; In one optional embodiment, in step S2, after coating is completed, the coating is dried and cured at a temperature of 40–150 °C for 0.5–12 h. In one optional implementation, step S1 includes the following steps: S11 First, dissolve the adhesive in a portion of an organic solvent to form an adhesive solution; S12. The conductive powder is added to the binder solution and stirred to disperse it to obtain a premix. S13 Add the remaining organic solvent to the premix and stir to disperse to obtain the supporting intermediate layer slurry.

[0021] In one optional embodiment, the resin layer comprises an ion exchange resin, a binder, and a conductive agent, wherein the mass ratio of the ion exchange resin, binder, and conductive agent is (50%~90%):(4.5%~30%):(0.5%~20%). The ion exchange resin of the positive electrode is OH. - The negative electrode uses an anion exchange resin of type H. + Type cation exchange resin.

[0022] In one optional embodiment, the particle size of the ion exchange resin is 100-1000 mesh; In one alternative embodiment, the adhesive comprises one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polysulfone (PSU); In one alternative embodiment, the conductive agent includes one or more of acetylene black, carbon fiber powder, carbon nanotubes, and Ketjen black.

[0023] In one optional embodiment, the method for preparing the resin layer includes the following steps: S1' ion exchange resin, conductive agent, binder and organic solvent are mixed to form ion exchange resin slurry; S2' The slurry is coated onto the surface of the support intermediate layer and cured to obtain a resin layer.

[0024] In one optional embodiment, the organic solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, and ethanol; In one optional embodiment, based on the total mass of the ion exchange resin, conductive agent, and binder, 0.5 to 6 mL of organic solvent is added for every 1 g of total raw materials. In one optional embodiment, in step S2', after coating is completed, the coating is dried and cured at a temperature of 40–120 °C for 0.5–6 h.

[0025] In a second aspect, the present invention provides an application method for an electrode pair as described in any of the above technical solutions, including a softening process and a regeneration process, wherein the softening process includes: introducing water to be treated into the water passage and softening the water under energized conditions; The regeneration process includes: switching the positive electrode of the softening process to the negative electrode, and vice versa, and then introducing water into the water passage to initiate the regeneration process. In one optional embodiment, the voltage corresponding to the regeneration process is greater than the voltage corresponding to the softening process. In one optional implementation, the voltage range of the softening process is 0.8 to 2V, and the voltage range of the regeneration process is 4 to 8V.

[0026] The technical solution of this invention has the following advantages: This invention improves the migration efficiency of ions in the water and the utilization efficiency of the electrode surface by setting a water flow channel between the positive and negative electrodes, allowing the water to flow along the channel under the influence of an electric field. The positive and negative electrodes are respectively equipped with OH groups. - Type anion exchange resin layer and H + The cation exchange resin layer enables the directional migration of anions and cations in the water under the influence of an electric field, allowing them to be removed by their respective resin layers, thereby enhancing the selectivity and efficiency of the water softening process. A catalyst layer is placed in the negative electrode, using a noble metal catalyst to promote the electrolysis reaction of water. This generates active ions in situ for resin regeneration during the operation and regeneration of the electrode pair, reducing dependence on external regeneration media and improving the regeneration efficiency of the resin layer and the recyclability of the electrode pair. Simultaneously, a supporting intermediate layer composed of conductive powder and binder is placed between the current collector and the resin layer. This ensures the conductivity of the electrode while enhancing the adhesion stability of the resin layer, reducing the risk of delamination due to water absorption and swelling of the resin material, and contributing to improved structural stability and service life of the electrode pair under long-term operating conditions. Attached Figure Description

[0027] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0028] Figure 1 This is a flowchart illustrating the preparation of the positive electrode in an embodiment of the present invention; Figure 2 This is a schematic diagram of the hierarchical structure of the positive electrode in an embodiment of the present invention; Figure 3This is a cross-sectional view of the hierarchical structure of the positive electrode in an embodiment of the present invention; Figure 4 This is a flowchart illustrating the preparation of the negative electrode in an embodiment of the present invention; Figure 5 This is a schematic diagram of the hierarchical structure of the negative electrode in an embodiment of the present invention; Figure 6 This is a cross-sectional view of the hierarchical structure of the negative electrode in an embodiment of the present invention; Figure 7 This is a schematic diagram of the softening process of the present invention; Figure 8 This is a schematic diagram of the regeneration process of the present invention.

[0029] Explanation of reference numerals in the attached figures: 1. Current collector; 2. Supporting intermediate layer; 3. Resin layer; 4. Catalyst layer. Detailed Implementation

[0030] The following embodiments are provided to better understand this application. However, the following embodiments do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining the features of this application with other prior art, falls within the scope of protection of this application.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having” and any variations thereof in the text of this application are intended to cover non-exclusive inclusion.

[0032] In the description of the embodiments of this application, the technical terms "first", "second", etc. are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0033] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0034] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0035] In the description of the embodiments of this application, the term "at least one" refers to one or more (including two).

[0036] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S1 and S2, indicating that the method may include steps S1 and S2 performed sequentially, or it may include steps S2 and S1 performed sequentially. For example, the method may also include step S3, indicating that step S3 may be added to the method in any order. For example, the method may include steps S1, S2, and S3, or it may include steps S1, S3, and S2, or it may include steps S3, S1, and S2, etc.

[0037] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0038] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way.

[0039] like Figures 1 to 8As shown, the present invention provides an electrode pair for water softening, including a positive electrode and a negative electrode arranged in pairs, with a water flow channel formed between the positive electrode and the negative electrode; the positive electrode includes a current collector 1 and a supporting intermediate layer 2 and a resin layer 3 sequentially attached to the current collector 1; the negative electrode includes a current collector 1 and a catalyst layer 4, a supporting intermediate layer 2 and a resin layer 3 sequentially attached to the current collector 1. The resin layer 3 of the positive electrode is OH - The anion exchange resin layer is of type H, and the resin layer 3 of the negative electrode is H + The cation exchange resin layer 2 includes a binder and conductive powder with a particle size of 100-800 mesh; the catalyst layer 4 includes a noble metal catalyst.

[0040] This invention provides a method for preparing positive and negative electrodes, as detailed below: (1) Preparation of positive electrode: ① Fabrication of the supporting intermediate layer 2 for the positive electrode: Conductive powder with a particle size of 100-800 mesh, including one or both of graphite powder and graphitized carbon fiber powder; The adhesive includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyethersulfone (PESU), polysulfone (PSU), and polyimide (PI); The mass ratio of conductive powder to binder is (50%~95%): (5%~50%). The wet thickness of the supporting intermediate layer 2 is 0.1~1mm; Organic solvents, including one or more of N,N-dimethylacetamide, N-methylpyrrolidone, and ethanol; based on the total raw material mass of conductive powder and binder, 0.5 to 6 mL of organic solvent is added for every 1 g of total raw material; The preparation method of the supporting intermediate layer 2 includes the following steps: S11. Dissolve the adhesive: Measure 50% to 90% of the total amount of solvent and place it in a container. Then weigh the adhesive and add it to the solvent. The adhesive can be left to stand for 1 to 6 hours to dissolve naturally, or it can be accelerated by stirring. S12. Weigh the conductive powder and add it to the binder solution in small amounts and multiple times. During the addition process, maintain a low stirring speed of 50 to 500 rpm. After all the solid mixture has been added, increase the stirring speed to 200 to 5000 rpm and continue stirring for 10 min to 2 h to ensure that the conductive powder is fully dispersed in the solvent system. S13. Reduce the stirring speed to 50-500 rpm, add the remaining 50%-10% of the solvent to adjust the slurry viscosity and improve its fluidity; After all the materials have been added, increase the stirring speed to 200-5000 rpm again and maintain high-speed stirring for 20 min to 6 h to ensure that the slurry system is fully homogeneous. If no obvious air bubbles are observed in the obtained slurry, it can be used directly for subsequent coating; if obvious air bubbles are present, ultrasonic degassing or vacuum degassing is used to remove air bubbles to obtain a support intermediate layer slurry for coating.

[0041] S2, Slurry Coating: The supporting intermediate layer slurry is coated using a coating tool, which can be a scraper or a coating machine; during coating, the wet coating thickness is controlled to be 0.1 to 1 mm, and the coating speed is controlled to be 0.5 to 50 cm / s; the slurry is coated on one side of the current collector 1 to form a wet supporting intermediate layer 2; After the slurry coating is completed, the wet current collector 1 is directly transferred to an environment of 40-150 ℃ for curing treatment. The curing time is 0.5-12 h, forming a support intermediate layer 2.

[0042] ②Preparation of the resin layer for the positive electrode: Ion exchange resin is OH - Type III anion exchange resin, using styrene-based strong basic anion exchange resin, supplied in OH form. - Type, total exchange capacity ≥3.8mmol / g; particle size 100~1000 mesh; Adhesives, including one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polysulfone (PSU); Conductive agents include one or more of acetylene black, carbon fiber powder, carbon nanotubes, and Ketjen black; the particle size of the conductive agent is less than or equal to 100 micrometers. The mass ratio of ion exchange resin, binder, and conductive agent is (50%~90%):(4.5%~30%):(0.5%~20%). Solvents, including one or more of N,N-dimethylacetamide, N-methylpyrrolidone, and ethanol; Based on the total mass of ion exchange resin, conductive agent, and binder, add 0.5 to 6 mL of organic solvent for every 1 g of total raw materials; The preparation method of resin layer 3 includes the following steps: S11' Dissolve the adhesive: Measure 50% to 90% of the total solvent volume and place it in a container. Then weigh the adhesive and add it to the solvent. The adhesive can be left to stand for 1 to 6 hours to dissolve naturally, or it can be accelerated by stirring. S12' Weigh the ion exchange resin and conductive agent and stir them thoroughly at a low speed of 50~200 rpm to obtain a uniformly distributed mixture of the two substances, which can avoid the problem of uneven mixing when the two substances are added separately. The mixed powder is added to the binder solution in small amounts and multiple times, while maintaining a low stirring speed of 150-500 rpm during the addition process; after all the solid mixture has been added, the stirring speed can be increased to 200-5000 rpm, and stirring can continue for 10 min to 2 h. S13', Reduce the stirring speed to 150-500 rpm, add the remaining 50%-10% of the solvent to adjust the slurry viscosity and improve its fluidity; After all the materials have been added, increase the stirring speed to 200-5000 rpm again and maintain high-speed stirring for 20 min to 6 h to ensure that the slurry system is fully homogeneous. If no obvious bubbles are observed in the obtained slurry, it can be used directly for subsequent coating; if obvious bubbles are present, ultrasonic degassing or vacuum degassing is used to remove bubbles to obtain a resin slurry for coating.

[0043] S2', Slurry coating: The resin slurry is coated using a coating tool, which can be a scraper or a coating machine; during coating, the wet coating thickness is controlled to be 0.2–0.8 mm, and the coating speed is controlled to be 0.5–50 cm / s; the slurry is coated on the surface of the supporting intermediate layer to form a wet resin layer; After the slurry coating is completed, the wet positive electrode is directly transferred to an environment of 40-120 °C for curing treatment. The curing time is 0.5-6 h to form resin layer 3.

[0044] (2) Preparation of negative electrode: ①Preparation of catalyst layer 4: Catalysts are noble metal catalysts, including one or more of the following: platinum, iridium, ruthenium, and their metal oxides. The catalyst is fixed on one side of the current collector 1 by spraying to form a catalyst layer 4 with a thickness of 0.05-50 μm. ②Preparation of the supporting intermediate layer 2 for the negative electrode: The method is the same as that used in step (1) to prepare the supporting intermediate layer 2 of the positive electrode, except that the slurry of the supporting intermediate layer 2 is coated on the catalyst layer 4.

[0045] ③Preparation of resin layer 3 for the negative electrode: The method for preparing the resin layer 3 of the positive electrode in step (1) is the same, except that "OH" is used instead of resin layer 3. - Replace "Type anion exchange resin" with "H" + "Type H+ cation exchange resin" refers to a styrene-based strong acid cation exchange resin, which is shipped in H+ form. + Type, with a total exchange capacity ≥4.0 mmol / g.

[0046] In this invention, one or more sets of electrode pairs can be set up, and a water flow channel is formed between adjacent positive and negative electrodes for water to pass through.

[0047] The present invention also provides a method for applying an electrode pair, including a softening process and a regeneration process.

[0048] The softening process includes: the paired positive and negative electrodes maintain their initial polarity, the positive electrode is connected to a positive potential, and the negative electrode is connected to a negative potential, forming a stable electric field between them; the water to be treated enters the water passage formed between the positive and negative electrodes from the inlet and flows along the water passage under the condition of energization.

[0049] Under the influence of an electric field, anions in the water migrate towards the positive electrode, while cations migrate towards the negative electrode. The anions that migrate to the surface of the positive electrode react with OH groups in the resin layer of the positive electrode. - The reaction mechanism of ion exchange in anion exchange resins can be represented as follows: Positive electrode: R-OH + anion → R-anion + OH- - Cations that migrate to the surface of the negative electrode react with H+ in the resin layer of the negative electrode. + The reaction mechanism of ion exchange in cation exchange resins can be represented as follows: Negative electrode: RH + cation → R- cation + H + ; OH released from the positive electrode - With H released from the negative electrode + Water is further formed within the water flow channel, and the reaction mechanism is as follows: OH - + H + → H2O; Through the aforementioned ion migration and exchange process, hardness ions and other anions and cations in the water are removed, resulting in softened product water. In one embodiment, the operating voltage corresponding to the softening process is denoted as V1, and its value ranges from 0.8 to 2 V.

[0050] The regeneration process includes: When the electrode pair reaches a certain adsorption state after softening operation, it enters the regeneration process. During the regeneration process, the electrode polarity is switched, so that the positive electrode in the softening process becomes the negative electrode, and the original negative electrode becomes the positive electrode. Water is then introduced into the water passage, and resin regeneration is carried out under energized conditions.

[0051] After the polarity switch, the original positive electrode becomes the negative electrode after the reversal, and its surface electrolyzes water under the action of an electric field. The reaction mechanism is as follows: Negative electrode after reversal: ① Electrolysis of water: 2H₂O + 2e⁻ - → H2 + 2OH - ; ② Regeneration reaction: R- anion + OH- - → R-OH + anion Simultaneously, the original negative electrode becomes the positive electrode after the reversal, and its surface electrolyzes water under the action of an electric field. The reaction mechanism is as follows: Positive electrode after reversal: ① Electrolysis of water: 2H₂O → O₂ + 4e⁻ - + 4H + ; ② Regeneration reaction: R-cation + H + → RH + cation.

[0052] Through the above-mentioned water electrolysis reaction and ion migration, OH- ions on the positive and negative electrodes... - Type I anion exchange resin and H + The cation exchange resins are restored to their initial OH and H states, respectively, achieving in-situ regeneration of the resin material and providing conditions for the next round of softening process.

[0053] In a preferred embodiment, the operating voltage corresponding to the regeneration process is greater than the operating voltage corresponding to the softening process, so as to ensure the functional differentiation between the softening process and the regeneration process under electrochemical conditions.

[0054] Specifically, the working voltage V1 of the softening process is used to drive ion migration and ion exchange, and its value ranges from 0.8 to 2 V; the working voltage of the regeneration process is used to drive the electrolysis reaction of water and generate H₂ for resin regeneration. + and OH - Its value ranges from 4 to 8 V.

[0055] Example 1 This embodiment provides a specific preparation method and application process for an electrode pair used for water softening. Details are as follows: (1) Preparation of positive electrode: ① Fabrication of the supporting intermediate layer for the positive electrode: Conductive powder with a particle size of 500 mesh, made from graphite powder; The adhesive used is polyvinylidene fluoride (PVDF). The mass ratio of conductive powder to binder is 85%:15%; The wet thickness of the supporting intermediate layer is 0.4 mm; Organic solvents, including one or more of N,N-dimethylacetamide, N-methylpyrrolidone, and ethanol; based on the total raw material mass of conductive powder and binder, 5 mL of organic solvent is added for every 1 g of total raw material; The method for preparing the supporting intermediate layer includes the following steps: S11. Dissolve the binder. Measure 70% of the total amount of solvent and place it in a container. Then weigh the binder and add it to the organic solvent. Use stirring to accelerate the dissolution. S12. Weigh the conductive powder and add it to the binder solution in small amounts and multiple times, while maintaining a low stirring speed of 200 rpm during the addition process; after all the solid mixture has been added, increase the stirring speed to 1000 rpm and continue stirring for 1 hour to ensure that the conductive powder is fully dispersed in the solvent system. S13. Reduce the stirring speed to 200 rpm and add the remaining 30% of the solvent to adjust the viscosity of the slurry and improve its flowability; After all the materials have been added, increase the stirring speed to 1000 rpm again and maintain high-speed stirring for 1 hour to ensure that the slurry system is fully homogeneous. If no obvious air bubbles are observed in the obtained slurry, it can be used directly for subsequent coating; if obvious air bubbles are present, ultrasonic degassing or vacuum degassing is used to remove air bubbles to obtain a support intermediate layer slurry for coating.

[0056] S2, Slurry Coating: The supporting intermediate layer slurry is applied using a coating tool, which can be a scraper or a coating machine; the wet coating thickness is controlled to be 0.4 mm and the coating speed is controlled to be 5 cm / s; the slurry is applied to one side of the current collector 1 to form a wet supporting intermediate layer; After the slurry coating is completed, the wet current collector 1 is directly transferred to an environment of 60°C for curing treatment. The curing time is 3 hours, forming a support intermediate layer.

[0057] ②Preparation of the resin layer for the positive electrode: Ion exchange resin is OH - The specific type of anion exchange resin selected is a styrene-based strong basic anion exchange resin, and the product is supplied in OH form. - Type, with a total exchange capacity ≥4.0 mmol / g and a particle size of 400 mesh; The adhesive used is polyvinylidene fluoride (PVDF). The conductive agent is acetylene black, and the particle size of the conductive agent is less than or equal to 100 micrometers. The mass ratio of ion exchange resin, binder, and conductive agent is 80%:10%:10%; The solvent used is N,N-dimethylacetamide; based on the total mass of the ion exchange resin, conductive agent, and binder, 4 mL of organic solvent is added for every 1 g of total raw materials. The method for preparing the resin layer includes the following steps: S11' Dissolve the adhesive. Measure 70% of the total amount of solvent and place it in a container. Then weigh the adhesive and add it to the solvent. Use stirring to accelerate the dissolution. S12' Weigh the ion exchange resin and conductive agent and stir them thoroughly at a low speed of 100 rpm to obtain a uniformly distributed mixture of the two substances, which can avoid the problem of uneven mixing when the two substances are added separately. The mixed powder is added to the binder solution in small amounts and multiple times, while maintaining a low stirring speed of 200 rpm during the addition process; after all the solid mixture has been added, the stirring speed can be increased to 1000 rpm and stirring can continue for 1 hour. S13' Reduce the stirring speed to 200 rpm and add the remaining 30% of the solvent to adjust the slurry viscosity and improve its flowability; After all the materials have been added, increase the stirring speed to 1000 rpm again and maintain high-speed stirring for 1 hour to ensure that the slurry system is fully homogeneous. If no obvious bubbles are observed in the obtained slurry, it can be used directly for subsequent coating; if obvious bubbles are present, ultrasonic degassing or vacuum degassing is used to remove bubbles to obtain a resin slurry for coating.

[0058] S2', Slurry coating: The resin slurry is applied using a coating tool, with the wet coating thickness controlled at 0.7 mm and the coating speed controlled at 25 cm / s; the slurry is applied to the surface of the support intermediate layer to form a wet resin layer. After the slurry coating is completed, the wet positive electrode is directly transferred to an environment of 80 ℃ for curing treatment. The curing time is 2 h to form a resin layer.

[0059] (2) Preparation of negative electrode: ① Preparation of catalyst layer: The catalyst used is platinum. The catalyst is fixed on one side of the current collector 1 by spraying to form a catalyst layer with a thickness of 10 μm; ②Preparation of the supporting intermediate layer for the negative electrode: The method is the same as that used in step (1) to prepare the supporting intermediate layer of the positive electrode, except that the slurry of the supporting intermediate layer is coated on the catalyst layer.

[0060] ③Preparation of the resin layer for the negative electrode: The method for preparing the resin layer of the positive electrode in step (1) is the same, except that "OH" is used instead of "OH". - Replace "Type anion exchange resin" with "H" + "Type cation exchange resin"; specifically, H + The cation exchange resin is a styrene-based strong acid cation exchange resin, and it is shipped in H... + Type, with a total exchange capacity of 4.0 mmol / g and a particle size of 400 mesh; (3) Application method of electrode pair: The prepared positive and negative electrodes are arranged in pairs, forming a water flow channel between them. During the softening process, the initial polarity of the positive and negative electrodes remains unchanged, and water to be treated is introduced into the water flow channel, and water softening is performed under energized conditions. In this embodiment, the DC voltage applied during the softening process is 1.5V.

[0061] After the electrode pair completes the softening process, the polarity of the positive and negative electrodes is switched, so that the positive electrode becomes the negative electrode and the negative electrode becomes the positive electrode during the softening process. Water is then introduced into the water passage for regeneration under energized conditions. In this embodiment, the DC voltage applied during the regeneration process is 5 V.

[0062] Example 2 The only difference between this embodiment and Embodiment 1 is that the conductive powder supporting the intermediate layer is graphitized carbon fiber powder.

[0063] Example 3 The only difference between this embodiment and Embodiment 1 is that the raw material ratio of the resin layer is different; in this embodiment, the mass ratio of ion exchange resin, binder and conductive agent is 70%:15%:15%.

[0064] Example 4 The only difference between this embodiment and Embodiment 1 is that the voltage for the softening process is 0.8V, and the voltage for the regeneration process is 4V.

[0065] Example 5 The only difference between this embodiment and Embodiment 1 is that the voltage for the softening process is 2V, and the voltage for the regeneration process is 8V.

[0066] Example 6 The only difference between this embodiment and Embodiment 1 is that the thickness of the catalyst layer is controlled to 0.5 μm by adjusting the spraying parameters.

[0067] Example 7 The only difference between this embodiment and Embodiment 1 is that the thickness of the catalyst layer is controlled to 0.05 μm by adjusting the spraying parameters.

[0068] Example 8 The only difference between this embodiment and Embodiment 1 is that the thickness of the catalyst layer is controlled to 50 μm by adjusting the spraying parameters.

[0069] Example 9 The only difference between this embodiment and Embodiment 1 is that the particle size of the conductive powder in the supporting intermediate layer is 100 mesh.

[0070] Example 10 The only difference between this embodiment and Embodiment 1 is that the particle size of the conductive powder in the supporting intermediate layer is 800 mesh.

[0071] Example 11 The only difference between this embodiment and Embodiment 1 is that the catalyst used in the catalyst layer is ruthenium.

[0072] Example 12 The only difference between this embodiment and Embodiment 1 is that the mass ratio of conductive powder to binder in the supporting intermediate layer is 50%:50%.

[0073] Example 13 The only difference between this embodiment and Embodiment 1 is that the mass ratio of conductive powder to binder in the supporting intermediate layer is 95%:5%.

[0074] Example 14 The only difference between this embodiment and Embodiment 1 is that the mass ratio of ion exchange resin, binder and conductive agent in the resin layer is 50%:30%:20%, and the particle size of the ion exchange resin is 100 mesh.

[0075] Example 15 The only difference between this embodiment and Embodiment 1 is that the mass ratio of ion exchange resin, binder and conductive agent in the resin layer is 90%:5%:5%, and the particle size of the ion exchange resin is 1000 mesh.

[0076] Comparative Example 1 The only difference between this comparative example and Example 14 is that: no catalyst layer is provided on the negative electrode, a supporting intermediate layer is directly provided on the current collector, and then a resin layer is provided on the supporting intermediate layer.

[0077] Test Example 1 To verify the performance of the water softening system provided by this invention in the water softening and regeneration process, the water softening systems in the embodiments and comparative examples of this invention were tested.

[0078] Test conditions: (1) Test conditions for operating mode: Source of hardness ions: calcium chloride; Test water preparation method: Calcium chloride is used as the hardness ion source. Deionized water is used to prepare calcium-containing hardness water samples. The water hardness is 100 mg / L in terms of calcium carbonate equivalent.

[0079] Operating voltage V1: 1.5V; Operating flow rate Q1: 15 mL / min; Operating mode: Continuous water supply; operation will stop when the cumulative water production reaches 2L. Test indicators: Measure the hardness of the produced water and calculate the hardness removal rate.

[0080] The test method for hardness of the produced water is as follows: GB / T 7477-2023 "Determination of Calcium and Magnesium in Water - EDTA Titration Method" The calculation method for hardness removal is: (raw water hardness - product water hardness) × product water volume.

[0081] (2) Regeneration mode test conditions Switch the test water to pure water; Regeneration voltage V2: 5 V; Regeneration flow rate Q2: 7.5 mL / min; Regeneration time: 60 min; Regeneration method: The positive electrode is switched to the negative electrode and the negative electrode is switched to the positive electrode during the softening process; After regeneration, the softening performance of the water softening systems in the embodiments and comparative examples was tested again under the above operating conditions.

[0082] It should be noted that, except for Examples 4 and 5, the other examples and comparative examples of the present invention were tested according to the above method; Example 4 is based on the above detection method, except that the voltage of the softening process is adjusted to 0.8V and the voltage of the regeneration process is adjusted to 4V.

[0083] Example 5 is based on the above detection method, except that the voltage of the softening process is adjusted to 2V and the voltage of the regeneration process is adjusted to 8V.

[0084] The test results are shown in Table 1 below: Table 1: Performance test results of water softening systems in the examples and comparative examples

[0085] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. An electrode pair for water softening, comprising a positive electrode and a negative electrode, characterized in that, A water flow channel is formed between the positive electrode and the negative electrode; The positive electrode comprises a current collector and a support intermediate layer and a resin layer attached to the current collector in sequence, and the negative electrode comprises a current collector and a catalyst layer, a support intermediate layer and a resin layer attached to the current collector in sequence; The resin layer of the positive electrode is OH - The resin layer of the negative electrode is H + The resin layer of the negative electrode is H The support intermediate layer includes a binder and a conductive powder having a particle size of 100-800 mesh.

2. An electrode pair for water softening according to claim 1, characterized in that, The thickness of the catalyst layer is 0.05-50 μm; And / or, the wet thickness of the support intermediate layer is 0.1-1 mm; And / or, the wet thickness of the resin layer is 0.2-0.8 mm; And / or, the catalyst layer comprises one or more of platinum, iridium, ruthenium, and metal oxides thereof; Preferably, the catalyst layer is fixed on the current collector by deposition, spraying or sintering.

3. An electrode pair for water softening according to claim 1, characterized in that, In the support intermediate layer, the mass ratio of the conductive powder and the binder is (50%-95%):(5%-50%); And / or, the conductive powder comprises one or both of graphite powder and graphitized carbon fiber powder; And / or, the binder comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylpyrrolidone, polyether sulfone, polysulfone and polyimide.

4. An electrode pair for water softening according to any one of claims 1-3, characterized in that, The preparation method of the support intermediate layer comprises the following steps: S1 mixing the conductive powder and the binder with an organic solvent to form a support intermediate layer slurry; S2 coating the support intermediate layer slurry on the surface of the current collector and curing to obtain the support intermediate layer.

5. An electrode pair for water softening according to claim 4, characterized in that The organic solvent comprises one or more of N,N-dimethylacetamide, N-methylpyrrolidone and ethanol; And / or, 0.5-6 mL of the organic solvent is added per 1 g of total raw materials of the conductive powder and the binder; And / or, in the step S2, after the coating is completed, drying and curing are performed at a temperature of 40-150 ℃ for 0.5-12 h; And / or, the step S1 comprises the following steps: S11 first dissolving the binder in part of the organic solvent to form a binder solution; S12 adding the conductive powder to the binder solution and stirring and dispersing to obtain a premix; S13 adding the remaining organic solvent to the premix and stirring and dispersing to obtain the support intermediate layer slurry.

6. An electrode pair for water softening according to claim 1, 2, 3 or 5, characterized in that The resin layer comprises ion exchange resin, binder and conductive agent, and the mass ratio of the ion exchange resin, the binder and the conductive agent is (50%-90%):(4.5%-30%):(0.5%-20%); wherein the ion exchange resin of the positive electrode is OH - the ion exchange resin of the negative electrode is H + the ion exchange resin of the negative electrode is H And / or, the particle size of the ion exchange resin is 100-1000 mesh; And / or, the binder comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene and polysulfone; And / or, the conductive agent comprises one or more of acetylene black, carbon fiber powder, carbon nanotube and ketjen black.

7. An electrode pair for water softening according to claim 6, characterized in that The preparation method of the resin layer comprises the following steps: S1' mixing the ion exchange resin, the conductive agent and the binder with an organic solvent to form an ion exchange resin slurry; S2' coating the slurry on the surface of the support intermediate layer and curing to obtain the resin layer.

8. An electrode pair for water softening according to claim 7, characterized in that The organic solvent comprises one or more of N,N-dimethylacetamide, N-methylpyrrolidone and ethanol; And / or, 0.5-6 mL of organic solvent is added per 1 g of total raw materials of ion exchange resin, conductive agent and binder; And / or, in the step S2', after coating, drying and curing is performed at a temperature of 40-120 ℃ for 0.5-6 h.

9. A method of using the electrode pair of any one of claims 1 to 8, characterized in that, The method comprises a softening process and a regeneration process, the softening process comprising: passing water to be treated into the water flow channel, and performing water quality softening under the condition of power supply; The regeneration process comprises: switching the positive electrode of the softening process to the negative electrode, switching the negative electrode to the positive electrode, passing water into the water flow channel, and entering the regeneration process.

10. The use according to claim 9, characterized in that, The voltage corresponding to the regeneration process is greater than the voltage corresponding to the softening process. And / or, the voltage range of the softening process is 0.8-2 V, and the voltage range of the regeneration process is 4-8 V.